Effect of Surface Biphilicity on FC-72 Flow Boiling in a Rectangular Minichannel - Aboubakri, Akam; Ahmadi, Vahid Ebrahimpour; Celik, Suleyman; Sadaghiani, Abdolali K.; Sefiane, Khellil; Kosar, Ali (Frontiers in Mechanical Engineering, 2021)
Flow boiling is one of the most effective mechanisms in heat transfer thanks to the latent heat of vaporization. Surface modifications such as mixed-wettability have a considerable effect on the boiling heat transfer performance in terms of enhancement in boiling heat transfer as well as critical heat flux. This study introduces a new method of fabrication of biphilic surfaces, where C4F8 (Octafluorocyclobutane) islands are surrounded by silicon. Two different biphilic surfaces were fabricated and compared with the entirely uniform hydrophobic surface taken as a reference,. Each of the biphilic surfaces has three different sections namely inlet, middle, and outlet regions. The first region is mainly hydrophobic (inlet), while the third region part is mainly hydrophilic (outlet). The heat transfer coefficients were obtained at different heat fluxes. Compared to the entirely uniform hydrophobic surface, the results show that biphilic surfaces enhance the boiling heat transfer performance by up to 50%. The visualization results revealed that the biphilic surfaces lead to more nucleation sites in the bubbly flow regime and break up the elongated bubbles in the slug flow regime.